Delay-dependent wide-area damping control for stability enhancement of HVDC/AC interconnected power systems. (April 2015) - Li, Yong; Liu, Fang; Cao, Yijia
Abstract: In this paper, a delay-dependent wide-area damping control strategy associated with a high-voltage direct current (HVDC) supplementary controller is presented to enhance the overall stability of parallel HVDC/AC interconnected systems. First, the HVDC/AC interconnected systems are linearized into a nominal delay-dependent linear model using varying-delay characteristics. Next, the robust H ∞ design approach is used to solve the optimal state-feedback-type controller parameters. All of the controller design problems are formulated in the framework of linear matrix inequalities (LMIs), which is convenient for converting the controller design problem into a standard nonlinear optimization problem represented as an optimization objective with a set of LMIs constraints. An iterative algorithm is presented to solve the optimization problem. The effects of the varying-delay of the wide-area signal on the damping performance are considered during the controller design. Additionally, the state observer is used to convert the state-feedback control into an output-feedback control that is convenient for practical applications. Two case studies are conducted on the Kundur׳s 4-machine 2-area system and the New England/New York interconnected system to validate the presented control concept and the designed HVDC wide-area damping controller.